A low-flux state in IRAS 00521−7054 seen with NuSTAR and XMM–Newton: relativistic reflection and an ultrafast outflow. Issue 2 (16th January 2019) - Walton, D J; Nardini, E; Gallo, L C; Reynolds, M T; Ricci, C; Dauser, T; Fabian, A C; García, J A; Harrison, F A; Risaliti, G; Stern, D
ABSTRACT: We present results from a deep, coordinated XMM–Newton  +  NuSTAR observation of the Seyfert 2 galaxy IRAS 00521−7054. The NuSTAR data provide the first detection of this source in high-energy X-rays ( E > 10 keV), and the broad-band data show this to be a highly complex source which exhibits relativistic reflection from the inner accretion disc, further reprocessing by more distant material, neutral absorption, and evidence for ionized absorption in an extreme, ultrafast outflow ($v$ out ∼ 0.4 c ). Based on lamppost disc reflection models, we find evidence that the central supermassive black hole is rapidly rotating ( a > 0.77), consistent with previous estimates from the profile of the relativistic iron line, and that the accretion disc is viewed at a fairly high inclination ( i ∼ 59°). Based on extensive simulations, we find the ultrafast outflow is detected at ∼4σ significance (or greater). We also estimate that the extreme outflow should be sufficient to power galaxy-scale feedback, and may even dominate the energetics of the total output from the system.